Oral doxycycline prevents skin-associated adverse effects induced by injectable collagenase in a rodent model of capsular contracture around silicone implants - Diehm, Yannick; Kotsougiani-Fischer, Dimitra; Porst, Elena; Haug, Valentin; Siegwart, Laura; Overhoff, Daniel; Kneser, Ulrich; Fischer, Sebastian (PLOS ONE, 2022)
Background: The collagenase of the bacterium Clostridium histolyticum (CCH) is already an established treatment for fibroproliferative diseases like M. Dupuytren and M. Peyronie Although results are comparable to surgical intervention, skin laceration is a severe and relevant side effect. Doxycycline (DOX) recently rose interest as an inhibitor of matrix-metalloproteinases alongside its capabilities of skin accumulation. It therefore might be a potential skin protective agent in the use of CCH. Methods: For simulation of a fibroproliferative disease adjacent to the skin, we utilized a rodent model of capsular fibrosis involving silicone implants and subsequent fibrotic capsule formation. For in-vitro studies, fibrotic capsules were excised and incubated with 0.9 mg/ml CCH and four different doses of DOX. For in-vivo experiments, animals received 0.0, 0.3 or 0.9 mg/ml CCH injections into the fibrotic capsules with or without prior oral DOX administration. Outcome analysis included histology, immunohistochemistry, gene expression analysis, chemical collagen and DOX concentration measurements as well as μCT imaging. Results: In-vitro, DOX showed a dose-dependent inhibition of CCH activity associated with increasing capsule thickness and collagen density and content. In-vivo, oral DOX administration did neither interfere with capsule formation nor in effectiveness of CCH dissolving fibrotic capsule tissue. However, skin thickness and especially collagen density was significantly higher compared to control groups. This led to a reduced rate of clinical skin lacerations after DOX administration. Conclusion: DOX inhibits CCH and accumulates in the skin. Thereby, DOX can effectively reduce skin laceration after CCH treatment.
Gesehen am 07.10.2022